(untitled) (Journal of the College of Basic Education, 2022)
Media discourse plays a salient role in the portrayal of Iraqi refugees who fled Iraq because of the continuity of war and violence which creates political, social and economic crises. The aim of this paper is to look critically at the most prominent strategies that are utilised by media news reports in representing Iraqi refugees along with the ideological viewpoint. This clarifies the significance of the language of media in developing the EFL cultural awareness and identifying the ideology-laden structures. Thus, the researchers examine the representation of Iraqi refugees in BBC News Reports from the perspective of critical discourse analysis. Accordingly, the researchers adopt Wodak’s (2001; 2009) discourse-historical approach and van Leeuwen’s (2008) sociological representation of social actors. The selected news report is analysed at two levels of analysis: linguistic and ideological. The researchers conclude that investigating the language of media can be implemented to promote the students’ awareness about issues connected to victimisation, abuse, reality and authority. By doing so, the students improve a deep insight of the global and cultural awareness in education relating to curriculum, hegemony, Eurocentric ideology in media discourse involving news reports and TV programs